2010
DOI: 10.1534/genetics.109.109892
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple Functional Domains of the Yeast l,3-β-Glucan Synthase Subunit Fks1p Revealed by Quantitative Phenotypic Analysis of Temperature-Sensitive Mutants

Abstract: The main filamentous structural component of the cell wall of the yeast Saccharomyces cerevisiae is 1,3-b-glucan, which is synthesized by a plasma membrane-localized enzyme called 1,3-b-glucan synthase (GS).Here we analyzed the quantitative cell morphology and biochemical properties of 10 different temperaturesensitive mutants of FKS1, a putative catalytic subunit of GS. To untangle their pleiotropic phenotypes, the mutants were classified into three functional groups. In the first group, mutants fail to synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 53 publications
5
49
0
2
Order By: Relevance
“…The temperature-sensitive FKS1 mutant (catalytic subunit of 1,3-␤-glucan synthase [32]) fks1-1154 loses its synthase activity at the restrictive temperature of 37°C due to an impaired supply of cell wall material to growing buds (33). As a consequence, fks1-1154 cells undergo budding cycle arrest with no or small-budded cells and, more interestingly, with duplicated and adjacent SPBs and replicated DNA, which is described as the cell wall integrity cell cycle checkpoint (3).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature-sensitive FKS1 mutant (catalytic subunit of 1,3-␤-glucan synthase [32]) fks1-1154 loses its synthase activity at the restrictive temperature of 37°C due to an impaired supply of cell wall material to growing buds (33). As a consequence, fks1-1154 cells undergo budding cycle arrest with no or small-budded cells and, more interestingly, with duplicated and adjacent SPBs and replicated DNA, which is described as the cell wall integrity cell cycle checkpoint (3).…”
Section: Resultsmentioning
confidence: 99%
“…Although the enzyme has not been purified to homogeneity, the central domain of partially purified Neurospora crassa Fks protein was shown to crosslink to azido-UDP-glucose (Schimoler-O' Rourke et al 2003), supporting the conclusion that this protein is the catalytic subunit. A recent functional analysis of FKS1 revealed that mutations in this central domain, which is predicted to be cytoplasmic, cause defects in GS activity (Okada et al 2010). Unlike loss of Pkc1, loss of Fks1/2 is not suppressed by increased osmotic support.…”
Section: Pkc1 and The Cwi Mapk Cascadementioning
confidence: 99%
“…A similar attempt to map the binding site for the substrate UDP-glucose using partially purified ␤-1,3-glucan synthase from Neurospora crassa also suffered from low specificity; however, among the cross-linked peptides were four clustered between residues equivalent to 1070 to 1273 in S. cerevisiae Fks1 (41). More recently, the characterization of temperature-sensitive S. cerevisiae mutants implicated specific Fks1 residues in ␤-1,3-glu-can synthase activity, as well as other phenotypes, including polarized growth and endocytosis (33).…”
mentioning
confidence: 99%